Tajik Basin and Southwestern Tian Shan, Northwestern India‐Asia Collision Zone: 2. Timing of Basin Inversion, Tian Shan Mountain Building, and Relation to Pamir‐Plateau Advance and Deep India‐Asia Indentation. Issue 5 (11th May 2020) - Abdulhameed, Sanaa; Ratschbacher, Lothar; Jonckheere, Raymond; Gągała, Łukasz; Enkelmann, Eva; Käßner, Alexandra; Kars, Myriam A. C.; Szulc, Adam; Kufner, Sofia‐Katerina; Schurr, Bernd; Ringenbach, Jean‐Claude; Nakapelyukh, Mykhaylo; et al.
Abstract: The Tajik basin and southwestern Tian Shan constitute the northwestern tip of the India‐Asia collision zone. Basin inversion formed the thin‐skinned Tajik fold‐thrust belt, outlined by westward convex fold trains, underlain by a décollement in Jurassic evaporites. The belt's leading edge—the Uzbek Gissar—and its transpressional northern lateral margin—the Tajik Gissar—constitute the thick‐skinned foreland buttresses. Apatite fission‐track data indicate 40‐ to 15‐Ma reheating by sediment burial in the Tian Shan. In the Gissar and the Tajik fold‐thrust belt, apatite fission‐track and (U, Th)/He ages date the major phase of shortening/erosion between 12 and 1 Ma, with exhumation to 2‐ to 3‐km crustal depths within a few Myr after onset of shortening. Shortening spread immediately across the fold‐thrust belt, typical for belts floored by a detachment in ductile rocks, and into the foreland buttresses. Reactivation concentrated in the internal (eastern) fold‐thrust belt with the thickest evaporates. The youngest ages ( 6.6–1.6 Ma) occur along the Vakhsh thrust, the active erosional front of the fold‐thrust belt in the northeastern Tajik basin, where it narrows between the converging Tian Shan and Pamir. Our study links major events in the Pamir hinterland with the Tajik basin and Tian Shan foreland. In the late Eocene–early Miocene, the advancing Pamir‐plateau crust loaded the foreland, inducing subsidence, reheating, and early shortening. Basin inversion and major shortening/transpression in the foreland buttresses from 12 Ma onward were synchronous with the subcrustal indentation of Indian lithosphere into the Tajik‐Tarim basin lithosphere and the onset of its rollback beneath the Pamir. Key Points: 40‐ to 15‐Ma sediment loading reheated the southern Tian Shan; major Tajik‐basin inversion and Tian Shan mountain building started at 12 Ma 12‐Ma shortening immediately spread to foreland buttresses and external fold‐thrust belt; reactivation affected its interior Tajik‐basin inversion and major Tian Shan mountain building were induced by lithospheric indentation of India into Asia beneath the Pamir